EKSISTENSI PENGRAJIN PARANG DI SUMBAWA : OPTIMALISASI PENGGUNAAN STRATEGI PEMASARAN - Andriani, Sri; Sri Nuryani, Hanifa (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2020)
Current Growth of Micro, Small and Medium Enterprises (MSMEs) in Indonesiatend to increase and contribute significantly indevelopment. On the other hand, this has caused a degree of competition in the MSME sector as wellwill increase. One of the MSMEs that still exists in Eastern Indonesia such asOne of the districts of Sumbawa is a machete craftsman. The purpose of this study is1) Identifying internal and external factors faced by machete craftsmenin the village of Batu Alang. 2) Formulate an alternative machete marketing strategy inBatu Alang village obtained based on the results of the analysis. 3) Determine prioritiesthe right marketing strategy for machete craftsmen in Batu Alang Villagerun his business. This research was conducted in Batu Alang Village, Moyo DistrictHulu uses descriptive methods and data collection is done by techniqueobservation and survey. Determination of respondents is done by survey techniques. That resultobtained, on the IFE matrix, the average value of the IFE is 3.012 while the EFE matrixamounted to 2,704. These results place machete craftsmen in the village of Batu Alangin cell IV called the grow and build strategy. In this position, formaintain its existence is possible to carry out intensive and strategyintegrative strategy.